Effect of Soy Isoflavones Supplementation on Adiponectin Levels in Postmenopausal Women: A Meta-Analysis - Tutunchi, Sara; Koushki, Mehdi; Amiri-Dashatan, Nasrin; Khodabandehloo, Hadi; Hosseini, Hossein; Panahi, Godratollah; Hashemi, Javad; Karbalaee-Hasani, Amir; Majidi, Ziba; Rezaei-Tavirani, Mostafa (Journal of Pharmacy and Nutrition Sciences, 2021)
Decreased adiponectin levels has been demonstrated in postmenopausal (PMP) women. Soy isoflavones, as an herbal product have been shown to increase adiponectin level but the results are inconclusive and inconsistent. The present study reassessed the data on the impact of soy isoflavones supplementation on adiponectin levels in PMP women through a meta-analysis. A systematic search was performed in the databases of PubMed, Web of science, Scopus and the Cochrane library. The literature search identified 830 studies with duplicates. Out of those, 80 were screened for title and abstract and 12 articles were ultimately selected for the analysis. Meta-regression and subgroup analyses, based on the moderator variables such as treatment duration, dose of soy isoflavones and BMI were performed. The quality of the studies was evaluated using the Grading of Recommendation Assessment, Development and Evaluation (GRADE) approach. The results revealed that soy isoflavones supplementation significantly increased the circulating level of adiponectin in PMP women (SMD: 0.36 µg/mL; 95% CI (0.05 to 0.66); P= 0.02). No publication bias was observed using Begg’s (P = 0.38) and Egger’s (P = 0.07) tests. Sensitivity analysis indicated the results were completely powerful and stable. Moreover, Meta-regression and subgroup analyses indicated a significant increase of adiponectin levels in subgroups of dose > 50 mg and treatment duration less or equal 3 months. Our findings showed significantly increase in adiponectin levels after isoflavones-supplemented soy consumption in postmenopausal women, who received dose > 50 mg of soy isoflavones in treatment duration ≤ 3 months.